2020
DOI: 10.1111/1471-0528.16366
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative hormonal treatment for prevention of endometrioma recurrence after ovarian cystectomy: a systematic review and network meta‐analysis

Abstract: Background The efficacy of hormonal regimens for the prevention of endometrioma recurrence in women who have undergone conservative surgery is still controversial. Objective To compare the efficacy of different hormonal regimens in this context and to rank them. Search strategy MEDLINE and Scopus databases were searched through January 2020. Selection criteria Randomised controlled trials (RCTs) or cohorts, comparing the effect of any pair of interventions (i.e. cyclic oral contraceptives [OC], continuous OC, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 57 publications
0
22
0
1
Order By: Relevance
“…Extrinsic adenomyosis is associated with more severe DIE lesions and higher ASRM scores. It will be beneficial for patients of coexistence of adenomyosis and endometriosis to apply individual management to achieve better efficacy ( 39 ). The coexistence of adenomyosis and endometriosis must be part of the decision-making process for DIE patients when they are presented on abnormal clinical symptoms and long-term infertility ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Extrinsic adenomyosis is associated with more severe DIE lesions and higher ASRM scores. It will be beneficial for patients of coexistence of adenomyosis and endometriosis to apply individual management to achieve better efficacy ( 39 ). The coexistence of adenomyosis and endometriosis must be part of the decision-making process for DIE patients when they are presented on abnormal clinical symptoms and long-term infertility ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…[ 20 ] According to a recent study, a short-term hormone therapy of <6 months is not effective in preventing recurrence. [ 16 ] Therefore, recent guidelines recommend implementing a maintenance therapy for at least 18 to 24 months after surgery. [ 21 ] For successful long-term maintenance therapy, not only the efficacy of treatment, but also the tolerability of treatment and the compliance of patients must be considered.…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent systematic literature review of randomized controlled studies, LNG-IUS can significantly reduce the risk of recurrence of pain symptoms [15] and endometrioma compared with place. [16] Many cohort studies comparing with other types of hormonal therapy have found that effects of LNG-IUS on pain relief and recurrence prevention are similar to those of combined oral contraceptives or dienogest. [17][18][19] The present study found that LNG-IUS was effective in preventing the recurrence of dysmenorrhea throughout a 10-year period and that its effect was similar to those of other types of hormone therapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, the study did not compare DNG maintenance treatment with other treatments, such as LNG-IUS or GnRH-a; therefore, it gave no liberty to choose a suitable treatment according to patient needs. Moreover, Wattanayingcharoenchai et al ( 19 ) suggested that there was no evidence supporting hormonal treatment for the postoperative prevention of endometriosis recurrence in the Network Meta-Analysis of RCTs. This was contrary to the evidence from cohort studies, which showed the protective effect of progesterone, especially for long-term management after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…DNG moderately inhibits the H-P-O axis, thereby inhibiting estrogen production ( 19 ). Similarly, it downregulates prostaglandin E2, inflammatory cytokines [including interleukin (IL)-6, IL-8, monocyte chemoattractant protein-1], estrogen synthetase aromatase, and neuroangiogenesis factors (such as vascular endothelial growth factor (VEGF) and nerve growth factor) in endometriotic cells to decrease recurrence and alleviate pain ( 19 , 20 ).…”
Section: Discussionmentioning
confidence: 99%